Oration at the Raising of "The Old Flag" at Sumter ;: and Sermon on the death of Abraham Lincoln, President of The United States - Beecher, Henry Ward (Alexander Ireland & Co., 1865)
Prefatory notes / J.H. Estcourt -- In memoriam / W.C. Bryant --Prefatory sketch / J.H. Estcourt -- Funeral epigraphs -- Appendix. President Lincoln's address at Gettysburg, 19th November, 1863.